PENGARUH DIMENSI ENDORSER CREDIBILITY DAN BRAND CREDIBILITY TERHADAP DIMENSI CONSUMER-BASED BRAND EQUITY - Hardjanti, Adiati; Siswanto, Hari (Jurnal Ilmiah Widya, 2014)
In a competitive marketing environment, company will generally make efforts to promote a product or service produced, to draw the attention of customers and creating a positive association so that prospective customers can be affected, always remember and compelled to try and in the end decided to purchase products offered. Advertising is the most frequently used media (especially consumer products) to communicate with consumers. The purpose of this study was to: (1) examine the positif influence of celebrity dimensions endorsement towards brand credibility, (2) examine the positif influence of endorser credibility dimensions and brand credibility toward consumer-based brand equity dimensions. The research design used in this study is hypothesis testing. This research used purposive sampling technique and overall of hypotheses tested by structural equation modeling using Amos 7.0 program. Data collected by distributing questionnaires to 150 respondents who have used and have seen advertisements Clear Men shampoo. It is concluded that (1) Dimensions Endorser Credibility positive effect on Brand Credibility (2) Some dimensions of Endorser Credibility positive effect on the dimensions of Consumer-Based Brand Equity, (3) Brand Credibility positive effect on the dimensions cosumer Based Brand Equity.